The Influence Of Public Policy On Community Subsectors: A Study On The Impact Of Economic And Educational Policies - Indriati Amirullah; Nurasia Natsir (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to evaluate the influence of public policy, especially in the fields of economics and education, on subsectors of society. Using a qualitative approach, this research explores people's perceptions and experiences regarding this public policy. The research results show that public policies often do not reflect the needs and conditions of society and can even have unexpected adverse impacts, such as increasing the cost of living due to economic policies or gaps in access to quality education due to educational policies. This research emphasizes the need to involve the public in the public policy-making process and the importance of effective communication between policymakers and the public to ensure that policies meet their objectives and bring benefits to society.